Further psychometric testing of an instrument to measure emotional care in hospital - Williams, Anne; Pienaar, C.; Toye, Christine; Joske, D.; Lester, L. (Wiley-Blackwell Publishing Ltd., 2011)
Aims and objectives: This paper describes further testing of the instrument Patient Evaluation of Emotional Care during Hospitalisation. Background: In 2005, a questionnaire was developed that could be completed by patients to evaluate the quality of emotional care received during their time in hospital. This questionnaire was tested at an acute care private hospital in Perth, Western Australia, with encouraging estimates of reliability and validity. The purpose of this study was to further test this questionnaire in a larger sample of inpatients at a public hospital in the same state. Design: Psychometric evaluation. Method: A hospital-wide survey of 13 wards of a public hospital was conducted. Two hundred and fifty-one patients completed the questionnaire. Results: Psychometric testing of the Patient Evaluation of Emotional Care during Hospitalisation demonstrated acceptable internal consistency reliability. Confirmatory factor analysis substantiated the four sub-scales as follows: Level of Security, Level of Knowing, Level of Personal Value and Level of Connection. The Level of Connection sub-scale was assessed for the first time in this study. This sub-scale had the lowest mean score of all the sub-scales across the hospital as well as in each of the wards surveyed. Qualitative data substantiated, from the patients’ perspective, a lack of connection with hospital staff.Conclusions: Further psychometric testing of the Patient Evaluation of Emotional Care during Hospitalisation instrument has confirmed its psychometric properties and usefulness as an instrument to measure emotional care during hospitalisation. Relevance to clinical practice: The Patient Evaluation of Emotional Care during Hospitalisation is a reliable and valid tool with which the emotional care of patients in hospital can be measured and the effectiveness of interventions assessed.